2016
DOI: 10.1007/s11250-016-1147-x
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy of the lymphoid organs and suppression of antibody response caused by velogenic Newcastle disease virus infection in chickens

Abstract: This project was undertaken to study the immunosuppressive capabilities of velogenic viscerotropic pathotype of Newcastle disease virus (VVNDV) infection in cockerels. Two hundred six-week-old cockerels were divided into four groups. Groups B/VUC and C/VC were vaccinated with LaSota in drinking water at 6 weeks of age. Groups C/VC and D/UC were challenged with VVNDV at 8 weeks of age. Three days post challenge (PC), the cockerels in group D/UC came down with clinical signs which included depression and greenis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…This obviously led to serious loss of some viral particles and the production of abnormally low mortalities of 0 and 30% in the layer chickens and broilers respectively. In our earlier experiments using this same virus at median embryo effective of 10 6.1 to 10 8.46 after 2-3 days storage at −40°C, we had mortalities of 76-100% in chickens and 60% in turkeys (Igwe et al 2014;Okpe et al 2015;Ezema et al 2016;Okoroafor et al 2017). Wakamatsu et al (2006) studied different strains of vvND virus infection in 4 and 6 weeks old chickens and reported 100% and 92% mortalities respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This obviously led to serious loss of some viral particles and the production of abnormally low mortalities of 0 and 30% in the layer chickens and broilers respectively. In our earlier experiments using this same virus at median embryo effective of 10 6.1 to 10 8.46 after 2-3 days storage at −40°C, we had mortalities of 76-100% in chickens and 60% in turkeys (Igwe et al 2014;Okpe et al 2015;Ezema et al 2016;Okoroafor et al 2017). Wakamatsu et al (2006) studied different strains of vvND virus infection in 4 and 6 weeks old chickens and reported 100% and 92% mortalities respectively.…”
Section: Discussionmentioning
confidence: 97%
“…There is severe atrophy of the lymphoid organs with severe necrosis and depletion of lymphocytes in the bursa, spleen and thymus (Igwe et al 2014;Okoroafor et al 2017). This may lead to immunosuppression (Ezema et al 2016). The histopathology of the velogenic viscerotropic ND (vvND) shows that the lymphocytes are the major cells that undergo necrosis just as in infectious bursal disease (IBD) (Brown et al 1999;Kommers et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…One major impetus for this work is the striking similarities between the lesions of vND and those of infectious bursal disease (IBD) of chickens. In both diseases, there are proventricular haemorrhages, caecal tonsil haemorrhagic ulcers, enteritis and severe atrophy of the bursa, spleen and thymus due to severe necrosis and depletion of the lymphocytes in the lymphoid organs (Okoye 1984;Mahgoub 2012;Ezema et al 2016;Sá e Silva et al 2016). In fact, in both diseases, the lymphocytes are the major cells that are destroyed.…”
Section: Discussionmentioning
confidence: 99%
“…IBD suppresses humoral antibody response in surviving chickens (Okoye 1984;Hoerr 2010;Mahgoub 2012). Evidence that vNDV infection is also immunosuppressive is gradually emerging as Ezema et al (2016) reported that experimental vNDV infection suppressed HI antibody response to La Sota vaccination in surviving chickens. It becomes interesting to find out if like in IBD the lymphocytes play any role in the establishment and severity of vNDV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation